2020
DOI: 10.1016/j.trac.2020.115984
|View full text |Cite
|
Sign up to set email alerts
|

The vision of point-of-care PCR tests for the COVID-19 pandemic and beyond

Abstract: Infectious diseases, such as the most recent case of coronavirus disease 2019, have brought the prospect of point-of-care (POC) diagnostic tests into the spotlight. A rapid, accurate, low-cost, and easy-to-use test in the field could stop epidemics before they develop into full-blown pandemics. Unfortunately, despite all the advances, it still does not exist. Here, we critically review the limited number of prototypes demonstrated to date that is based on a polymerase chain reaction (PCR) and has come close to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 101 publications
(127 reference statements)
0
71
0
Order By: Relevance
“…On the other hand, the use of pseudovirus expressing the S protein of SARS-CoV-2 instead of the virus itself is also a great opportunity to simplify and accelerate the development of assays [38] for viral proteins. The integration of technologies to smartphone mobile devices [30] , [31] , [40] , [117] , [118] , [193] provides new opportunities in different areas. In the field of medical diagnostics, they represent a paradigm shift [193] that allows the provision of mobile health care and personalized medicine.…”
Section: Others Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of pseudovirus expressing the S protein of SARS-CoV-2 instead of the virus itself is also a great opportunity to simplify and accelerate the development of assays [38] for viral proteins. The integration of technologies to smartphone mobile devices [30] , [31] , [40] , [117] , [118] , [193] provides new opportunities in different areas. In the field of medical diagnostics, they represent a paradigm shift [193] that allows the provision of mobile health care and personalized medicine.…”
Section: Others Approachesmentioning
confidence: 99%
“…within the beginning of the pandemic to August 2020. Table S1 (supplementary material) presents a classification of the published reviews based on their main purposes: (i) reviews and minireviews about the main advances carried out in the diagnostic tests in the last months, together with a critical discussion about their utility [2] , [3] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ; (ii) information about the biosensors and the nanotechnology is presented as a useful tool to develop new strategies for the detection of the infection and also for its treatment [8] , [11] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ; (iii) different point of view about how the artificial intelligence (AI) can be presented as a versatile tool to control the pandemic and, even more interesting, in containing the spread of the virus [20] , [68] , [69] ; (iv) current and update information about the structure and genomic of SARS-CoV-2 [70] , [71] , [72] , [73] ...…”
Section: Introductionmentioning
confidence: 99%
“…For example, the COVID-19 pandemic has highlighted the importance of rapid molecular testing for pathogen detection ( 2 ). Toward that aim, recent studies have demonstrated that common molecular diagnostic tools, such as RT-PCR and DNA melting analysis, can be performed in minutes-to-seconds ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several low cost immunoassays and molecular diagnostic kits, including Abbott's ID NOWTM, Lumex Instruments' Microchip RT-PCR and Roche's Cobas, etc., have been developed[ [65] , [66] , [67] , [68] ]. However, serological tests are used as a surveillance technique to understand better the epidemiology of the population-wide immunity environment of COVID-19[ 69 ].…”
Section: Covid-19 Virus-host Interaction Mechanismmentioning
confidence: 99%